A comparative study of sEMG signal of the symmetrical pectoral major muscle in bench press exercise using Smith machine and free weights - Hamdan, Abdullah Ghazi; Altay, Usama (Journal of Physical Education, 2020)
The study aimed to measure the electrical activity (mean and peak) of the pectoral major muscle of the right and left side in bench press exercise using the free weights and Smith machine to identify the differences in the electrical activity in the intensity (50%, 75%, and 100%) of (1RM). The researcher used the experimental method. The subject was four students who are practicing weightlifting sport in the College of Physical Education and Sports Sciences / University of Baghdad. Their body mass were (69.38 ± 5.56) kg, height (171.52 ± 1.15) cm, and age (20.25 ± 2.25) years. Bench press test was performed on the flat level, and then the same previous test carried out again, but using Smith machine with the intensity of (50%, 75%, and 100%) of (1RM) for both tests. The researchers used the SPSS to obtain the results by using t-test for independent samples. The results did not show significant differences between the right and left pectoral major muscle in sEMG signal (mean and peak) when using free weights and smith machine. The increasing in the electrical activity (mean and peak) associated with increasing in intensity for both pectoral major muscle. the rustles showed significant differences in the right pectoral major muscle for using free weight, and a significant differences in the left pectoral major muscle for using smith machine. The researchers recommended the use of smith machine or free weights to develop the pectoral major muscle.